How Can We Identify Hijacked Journals? - Mehdi Dadkhah; Marwan M. Obeidat; Mohammad Davarpanah Jazi; Tole Sutikno; Munawar A Riyadi (Institute of Advanced Engineering and Science, 2015)
By developing research and academic centers, the number of performed research articles has also increased. On the other hand, publishing the results of these articles in scientific journals shall also grow. In the meantime, researchers are trying to publish the findings of their research in journals which have been approved by one or more international indices so that such findings can be seen. In order to enhance the academic standards of Universities, proper journal choice will be of interest to researchers, especially those that are indexed in websites such as Thomson Reuters. However, certain forgery frauds researchers by launching fake Web sites that have been named by academic journal titles. In this paper, we introduce an approach to identify this type of journals that will be applicable by researchers in various academic disciplines.